2010
DOI: 10.1016/j.chemosphere.2010.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia fate of petroleum hydrocarbons in the soil: Oil matrix of constructed biopiles

Abstract: A dynamic multimedia fugacity model was used to evaluate the partitioning and fate of petroleum hydrocarbon fractions and aromatic indicator compounds within the soil: oil matrix of three biopiles. Each biopile was characterised by four compartments: air, water, soil solids and non-aqueous phase liquid (NAPL). Equilibrium partitioning in biopile A and B suggested that most fractions resided in the NAPL, with the exception of the aromatic fraction with an equivalent carbon number from 5 to 7 (EC(5-7)). In Biopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…At the depth of 5 cm, Decane was detected after two days and in 10 cm after 28 days under 0.32 ppm crude oil treatment. These findings agreed with that reported by Coulon et al (2010) who concluded that the mobility of hydrocarbons fractions in the soil was governed by its leaching factors (special parameters of hydrocarbons) which were very high in Decane and Undecane hydrocarbon fractions. Figure 3 shows the percent recovery of Tridecane at different soil depths under different crude oil treatments and different intervals of time.…”
supporting
confidence: 95%
“…At the depth of 5 cm, Decane was detected after two days and in 10 cm after 28 days under 0.32 ppm crude oil treatment. These findings agreed with that reported by Coulon et al (2010) who concluded that the mobility of hydrocarbons fractions in the soil was governed by its leaching factors (special parameters of hydrocarbons) which were very high in Decane and Undecane hydrocarbon fractions. Figure 3 shows the percent recovery of Tridecane at different soil depths under different crude oil treatments and different intervals of time.…”
supporting
confidence: 95%
“…It is known that asphaltenes prefer to aggregate in aqueous and organic solvents, which results in porous networks sequestrating small oil molecules (Li et al, 2012b). Large scale aggregation of asphaltenes is adverse for oil removal because it (i) alters the surface hydrophobicity and increases the mass transfer resistance for the release of light oil fractions during physical removal, and (ii) forms a thick and viscous non-aqueous phase liquid hindering the biodegradation due to the lack of water, oxygen and nutrients (Coulon et al, 2010). Although various numerical models have been developed to predict oil fate such as the Monte Carlo based nonlinear dynamic program (Li et al, 2014), the lattice Boltzmann based large-scale oil spill model (Maslo et al, 2014) and the Eulerian-Lagrangean cross-scale oil spill model (Azevedo et al, 2014), the effects of asphaltene aggregation on the overall environmental risks were not well incorporated into these models.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption and aggregation of asphaltenes on mineral surface would result in a thick and viscous non-aqueous phase liquid (NAPL). Previous studies indicated that the NAPL was the most dominant compartment for the distribution of petroleum hydrocarbons (Coulon et al, 2010) and the retention time of PAHs in the NAPL was at least 3-fold longer than in the others phases (Pollard et al, 2008). Therefore, drawing on a comprehensive understanding of asphaltene aggregation on the clay surface is of particular interest for developing a realistic environmental risk assessment framework for oil contaminated soils.…”
Section: Introductionmentioning
confidence: 98%